THE USE OF METACOGNITIVE STRATEGY AND STUDENTS’ ENGLISH ACHIEVEMENT - Neman, Meily Ivane Esther; Rolangon, Michelle Theresia (Fakultas Keguruan dan Ilmu Pendidikan, 2024)
This study investigated the correlation between students' use of metacognitive strategies and their English achievement in grade XI Science at SMA Advent UNKLAB. The study aimed to explore the level of metacognitive strategy use among students, assess their English achievement, and determined if there is a significant correlation between metacognitive strategy use and English achievement. The research employed a quantitative approach, utilizing descriptive and correlational methods. Data was collected through a questionnaire adapted from Bessai (2018) to measure metacognitive strategy use, and English mid-test results are used for academic achievement. The study includes 118 students from four different classes in grade XI Science. The findings revealed that students exhibit a high level of metacognitive strategy use, with a mean score of 3.71. Additionally, their English achievement is considered good, with an average score of 86. The Pearson correlation coefficient indicated a significant positive correlation (r = 0.374, p = 0.001) between students' metacognitive strategy use and their English achievement. In conclusion, this study recommended that teachers motivate students to use metacognitive strategies for learning English. Further investigations in different school environments and grade levels are suggested for a deeper understanding of this relationship.